PENERAPAN METODE TOPSIS SEBAGAI PENGUKURAN DALAM PENETAPAN KANDIDAT CALON PENERIMA KIP PADA PERGURUAN TINGGI SWASTA (PTS) - Eva Julia Gunawati Harianja (Universitas Methodist Indonesia, 2021)
Education and teaching are the rights of every citizen as regulated in the 1945 Constitution which is written in article 31, paragraph (1). However, the high cost of education sometimes becomes an obstacle for economically disadvantaged people, so that many secondary graduates are unable to continue their education to higher education even though they have good academic potential. The government has tried to provide a solution to this problem by organizing the Smart Indonesia Program (PIP) in helping its citizens obtain the right to higher education, namely through the provision of KIP Lectures that can be submitted by students at PTN and PTS. Private universities which act as facilitators for students in submitting KIP Lecture applications are expected to be more selective in the candidate selection process so that the distribution of assistance is right on target. Determination of KIP Lecture recipients based on certain criteria is often a problem in the decision-making process. To express the preferences of decision makers on the most desirable alternative, it can be done by applying the Technique For Order Preference by Similarity to Ideal Solution (TOPSIS). The TOPSIS method will be combined with fuzzy logic to determine the weight value for each criterion attribute, followed by a ranking process to select the best alternative, in this case a valid alternative as a beneficiary that fits the criteria. With this method, it is hoped that the assessment process will be more precise and accurate because it is based on predetermined criteria and weights. Keywords:,